Basal-like breast cancer: The road less traveled. - Bhanvadia, Viral M; Goyal, Prashant (Annals of Pathology and Laboratory Medicine, 2014)
Basal like breast cancer is a heterogeneous subtype having poor disease free and overall survival and distinct type of recurrence and metastasis, identified by gene expression profile study. Current chemotherapy fails to curtail the innate aggressive behavior in the majority of patients. The poor prognosis coupled with a lack of targeted use of therapies is reflected in the high mortality. Future research work will be directed upon better understanding of this entity for tailored therapy.